Novelties on Lippia sect. Goniostachyum (Verbenaceae): a new variety from the Brazilian Cerrado and additional nomenclatural and taxonomic notes - Cardoso, Pedro Henrique; Menini Neto, Luiz; Trovó, Marcelo; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2020)
Lippia stachyoides var. guajajarana, a new variety of Verbenaceae endemic from the Emas National Park, Goiás State, is described and illustrated. The new variety belongs to L. sect. Goniostachyum, which is characterized by numerous florescences per leaf axil and tetrastichous floral bracts. A detailed diagnosis, comparison with morphologically similar taxa, a key to the species and varieties from the section, plus habitat information, illustration, and a conservation status assessment are provided. Furthermore, L. morii is included in L. sect. Goniostachyum based on morphological traits and L. rivalis is considered a new synonym of L. origanoides. Lectotypes are designated for L. morii and L. rivalis, contributing to the taxonomy and nomenclature of the section.